Usability Analysis of the Sahabatku Application using the System Usability Scale - Tissa Maharani (International Journal Science and Technology, 2025)
After COVID-19, various mental health issues have been increasing. This is where the important role of information technology comes in, one of which is in the implementation of counseling, which has shifted from face-to-face to online. The Sahabatku application is one of the psychological counseling applications created as an effort to improve mental health. The purpose of this study is to identify the usability value of the Sahabatku application so that it can provide development ideas for developers in the future and to ensure that users of the application are satisfied as they achieve their counseling goals. This research took place from November 2024 to February 2025, using a System Usability Scale questionnaire consisting of 10 questions with a Likert scale of 1-5 to 61 students aged 17-21 majoring in psychology who had never used the application at all. This study concludes that the Sahabatku application received SUS score of 64, placing it at Grade C-, the Adjective scale is rated as OK, the Acceptability scale is marginally accepted, and the NPS score is classified as passive.